Flow image velocimetry method based on advection-diffusion equation - Bizjan, Benjamin (Strojniški vestnik, 2014)
This paper presents a non-contact method for velocity field calculation from a series of fluid flow images with illuminated planar layer of the flow and a mixed-in pollutant for flow visualization. The velocity field is calculated using a model similar to optical flow that is based on the advection-diffusion equation. The model is evaluated using a set of synthetic airfoil flow visualization images generated by a combination of computational fluid dynamics and inverse advection-diffusion equation approaches. The calculated velocity fields are in a good agreement with the true velocity fields.
Keywords: advekcijsko-difuzijska enačba; hitrostno polje; izračun gostega tokovnega polja; optični tok; računalniška dinamika tekočin; računalniško podprta vizualizacija